Complex partial seizures: EEG foci and response to carbamazepine and sodium valproate. Issue 10 (October 1985) - Gupta, A K; Jeavons, P M
Abstract : The EEG and clinical records were reviewed of 85 subjects who had been treated for complex partial seizures with carbamazepine alone or with a combination of carbamazepine and sodium valproate. There was a correlation between the site of the EEG abnormality and the therapeutic response to anticonvulsant therapy. Subjects who had a left sided temporal lobe EEG abnormality responded better to carbamazepine alone, while those who had an abnormality on the right responded to a combination of carbamazepine and sodium valproate.